Dental care trajectories among formerly incarcerated older adults in the United States - Alexander Testa; Luis Mijares; Mateus Renno Santos; Vahed Maroufy; Dylan B. Jackson; Rafael Samper-Ternent; Rahma Mungia; Ana C. Neumann (PLoS ONE, 2025)
A growing body of research has documented an association between prior incarceration and lower dental care use, yet the longitudinal impact of prior incarceration on dental care patterns over time among older adults remains unexplored. This study aims to investigate whether prior incarceration is associated with differing trajectories of dental care use among older adults in the United States. Data were drawn from the 2012-2020 waves of the Health and Retirement Study (HRS), a nationally representative longitudinal survey of older adults in the United States (n =  5,893). Group-based trajectory modeling was used to estimate dental care use patterns over time. The findings revealed dental care patterns followed three trajectories: regular dental care use (48.1%), moderate-declining dental care use (27.3%), and low dental care use (24.6%). Multinomial logistic regression was used to examine the relationship between prior incarceration and membership in these trajectory groups. Bivariate analyses revealed that prior incarceration was significantly associated with higher relative risks of being in the moderate-declining (Relative Risk Ratio [RRR] =  2.75, 95% CI =  2.08-3.63) and low dental care use trajectories (RRR =  2.88, 95% CI =  2.10-3.94) compared to the regular dental care use group. After adjusting for sociodemographic, economic, and healthcare-related covariates, formerly incarcerated individuals had a 1.52 times higher relative risk of belonging to the moderate-declining dental care trajectory (RRR =  1.52, 95% CI =  1.16–1.98). The association between prior incarceration and membership in the low dental care trajectory group was not statistically significant. These findings underscore the need for targeted interventions to address dental care disparities among formerly incarcerated individuals, which could lead to improved oral and overall health outcomes for this vulnerable population.